Research and Prospect of Fishery Resource Survey Technology - Ma, Wenjing; Xu, Kaida (International Journal of Natural Resources and Environmental Studies, 2024)
At present, the sustainable utilization of fishery resources has become a hot topic in the study of fishery sustainable development, and it is also an important research content in the theory and practice of sustainable development. In the 21st century, in addition to climate change and other factors, a large number of artificial Marine economic activities have caused great damage to the ecological environment of the habitat of fishery resources. At present, the protection of fishery resources is imminent, and to protect fishery resources, we need to conduct a good survey of existing fish. Based on the survey technology of fish resources, this paper introduces the traditional survey technology and modern fish resources survey technology in detail, analyzes the existing problems and countermeasures, and provides reference for the study of fish resources survey.